O que e como escrevemos na web: um estudo multidimensional de variação de registro em língua inglesa - Mayer, Cristina (2018)
The main goal of this research was to look at Web text varieties, specifically in social networks and consumer generated content such as comments, reviews and complaints in English through the Multidimensional Approach (MD) for register variation analysis leading to a set of dimensions of variation across Web registers. Web registers have been the object of several MD investigations (BERBER SARDINHA, 2014; BIBER et al., 2015; BIBER; EGBERT, 2015, 2016); however, these studies have not focused on social networks and consumer generated content. To fill this gap, a corpus of 15 of these registers was designed and compiled, the CoUGC – Corpus of User Generated Content, and three separate multidimensional analyses (MD) were conducted on the corpus, as well as a canonical correlation analysis. The first one was the additive MD analysis, in which the registers were added to the Dimensions of Variation of English by Biber (1988). The second one was a ‘mainstream’ MD analysis, in which the coocurrence of lexicogrammatical variables was analyzed and 4 dimensions were interpreted, representing the functional parameters underlying the variation across the registers. The third analysis, in turn, was based on the traditional MD analysis; however, it was conducted with lexical variables (BERBER SARDINHA, 2014; 2017; no prelo). This analysis revealed 5 thematic dimensions, which reflected semantic groupings. A canonical correlation analysis was then run to explain the relationship between the functional and lexical dimensions. All the analyzes led to the study of the use of the language by Web users